Pola Asuh Kyai Dalam Mempersiapkan Generasi Penerus (Studi Kasus Pengasuh Pondok Pesantren Hidayatul Mubtadi-Aat Al-Qur’aniyyah (HMQ) Kediri) - Sifa Syahidah (JMPT: Jurnal Manajemen Pendidikan Tihamah, 2023)
Parenting is fundamental in the formation of character. Exemplary parental attitudes are needed for children's development because children will do modeling and imitation of their immediate environment. This research is a qualitative descriptive research using a case study method or approach. This research focuses intensively on one particular object that is studied as a case. The formation of parenting styles in Islamic boarding schools and families has a central role in shaping the character and development of children. In Islamic boarding schools, Islamic religious values ​​and principles are the main foundation of parenting, in the family, parenting is influenced by cultural and religious values ​​which are the foundation for the formation of children's character.